Mosque Development Strategy Based on Religious Tourism in Jami' Pekojan Mosque Semarang - Savitri, Fania Mutiara; Karim, Abdul; Muhtadin, Badrus Saufil (Munazzama: Journal of Islamic Management and Pilgrimage, 2022)
This study aims to determine the potential of the Jami' Pekojan Mosque Semarang and to know the strategy for developing a mosque based on religious tourism at the Jami' Pekojan Mosque Semarang. This study used qualitative research. The researchers used primary data and secondary data sources to obtain the data needed. For data collection techniques, the researchers used interviews, observation methods, and documentation methods. This study used the theory of Milles and Huberman for data analysis techniques, with the flow of data reduction, data presentation, and drawing conclusions. The results showed that the Jami' Pekojan Mosque Semarang was one of the religious tourism objects located in the city of Semarang, Central Java. This tourist attraction had architectural beauty in the form of ancient buildings that could be used as a means of historical education for visitors. The potential of Jami' Pekojan Mosque Semarang had its own attraction for visitors. These potentials included the Cultural Heritage Mosque, the Tomb of Syarifah Fatimah bint Husain Al-Aidrus, and the Indian Porridge Tradition. The development of religious tourism at the Jami' Pekojan Mosque in Semarang on internal aspects needed to be carried out, such as the formation of tourism management employees and job desk distribution, providing local tour guide facilities, making improvements, maintaining and taking care of tourists attractions and completeness of facilities and infrastructure, creating attraction innovation for visitors, continuing to carry out their duties as much as possible. Meanwhile, on the external aspect, the management could explore media publications, do branding mosques based on religious tourism in the middle of Semarang City, cooperate with tour guides association, and using social media for promotion.***Dalam penelitian ini bertujuan mengetahui potensi yang dimiliki Masjid Jami’ Pekojan Semarang dan mengatahui strategi pengembangan masjid berbasis wisata religi di Masjid Jami’ Pekojan Semarang. Penelitian ini menggunakan penelitian kualitatif, untuk mendapatkan data yang diperlukan peneliti menggunakan sumber data primer dan data sekunder. Untuk tekhnik pengambilan datanya menggunakan metode wawancara, metode observasi, dan metode dokumentasi. Penelitian ini menggunakan teori Milles dan Huberman untuk teknik analisis data, dengan alur reduksi data, penyajian data, dan penarikan kesimpulan. Hasil Penelitian menunjukan bahwa Masjid Jami’ Pekojan Semarang merupakan salah satu objek wisata religi yang berada di Kota Semarang, Jawa Tengah. Objek wisata ini memiliki keindahan arsitektur berupa bangunan kuno yang dapat dijadikan sebagai sarana edukasi sejarah bagi pengunjung. Potensi yang ada menjadikan Masjid Jami’ Pekojan Semarang memiliki daya tarik tersendiri bagi pengunjung. Potensi tersebut meliputi: Masjid Cagar Budaya, Makam Syarifah Fatimah binti Husain Al-Aidrus, Tradisi Bubur India. Pengembangan wisata religi Masjid Jami’ Pekojan Semarang pada aspek-aspek internal perlu dilakukan, yakni Pembentukan struktur pegawai pengelola wisata dan pembagian jobdesk, Memberikan fasilitas pemandu wisata (tour guide) lokal, Melakukan perbaikan fasilitas, Menjaga dan merawat daya tarik wisata serta kelengkapan sarana dan prasarana, Inovasi daya tarik pengunjung, tetap menjalankan tugas semaksimal mungkin. Sedangkan pada aspek eksternal yakni pihak pengelola bisa bekerjasama dengan media publikasi, melakukan branding masjid berbasis wisata religi yang berada ditengah Kota Semarang, bekerjasama dengan pihak asosiasi pemandu wisata, melakukan promosi menggunakan media sosial.Keywords: Development, Mosques, Religious tourism.